2014
DOI: 10.3892/ijo.2014.2335
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane and TRAIL induce a synergistic elimination of advanced prostate cancer stem-like cells

Abstract: Advanced androgen-independent prostate cancer (AIPC) is an aggressive malignancy with a poor prognosis. Apoptosis-resistant cancer stem cells (CSCs) have been identified in AIPC and are not eliminated by current therapeutics. Novel therapeutic options, which are currently being evaluated in patient studies, include TRAIL and the broccoli-derived isothiocyanate sulforaphane. Although neither agent targets normal cells, TRAIL induces apoptosis in most cancer cells, and sulforaphane eliminates CSCs. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 49 publications
(37 reference statements)
1
45
1
Order By: Relevance
“…Numerous natural compounds such as wogonin (derived from the popular Chinese herb Huang-Qin), sulforaphane (derived from enriched broccoli sprout extracts), and melittin (major component of bee venom) sensitize resistant malignant cells to TRAIL-induced apoptosis through the modulation of NF-iB signaling pathway. [102][103][104] Upregulation of TRAIL receptors through NF-kB is also mediated by other natural compounds such as the ethanolic extract of Brazilian green propolis (EEP) and curcumin (a substance found in turmeric). 105,106 However, kurarinone (a natural bioactive lavandulyl flavonoid), 107 resveratrol (a type of natural phenol), 108 artesunate (a derivative of the natural product artemisinin), 109 and combertastatin A-4 (isolated from the bark of combretum caffrum) 110 can also sensitize melanomas to TRAIL through abrogating TRAIL-induced NF-kB activation and modulation of expression of anti-apoptotic genes such as cFLIP, XIAP, and Bcl-xL.…”
Section: Natural Compounds That Can Sensitize Tumor Cells To Trailmentioning
confidence: 99%
“…Numerous natural compounds such as wogonin (derived from the popular Chinese herb Huang-Qin), sulforaphane (derived from enriched broccoli sprout extracts), and melittin (major component of bee venom) sensitize resistant malignant cells to TRAIL-induced apoptosis through the modulation of NF-iB signaling pathway. [102][103][104] Upregulation of TRAIL receptors through NF-kB is also mediated by other natural compounds such as the ethanolic extract of Brazilian green propolis (EEP) and curcumin (a substance found in turmeric). 105,106 However, kurarinone (a natural bioactive lavandulyl flavonoid), 107 resveratrol (a type of natural phenol), 108 artesunate (a derivative of the natural product artemisinin), 109 and combertastatin A-4 (isolated from the bark of combretum caffrum) 110 can also sensitize melanomas to TRAIL through abrogating TRAIL-induced NF-kB activation and modulation of expression of anti-apoptotic genes such as cFLIP, XIAP, and Bcl-xL.…”
Section: Natural Compounds That Can Sensitize Tumor Cells To Trailmentioning
confidence: 99%
“…The therapies focused on inhibiting self-renewal of cancer stem cells, inducing their differentiation or targeting their cell-surface molecular markers [15,47,48]. However, treatment strategies with existing anti-cancer agents like cisplatin, oxaliplatin and 5-fluorouracil were reported to enhance cell viability and promote the self-renewal and survival of cancer stem cells in different cancer models [49][50][51]. This constitutes the basis of tumor recurrence observed in many patients who undergo conventional chemotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…In another study, combination of sulforaphane and recombinant soluble TRAIL was found to be superior to single treatment in reducing tumor growth and CSCs marker expression in the xenotransplantation model of androgen-independent prostate cancer (PC3) cells into chorioallantoic membrane of fertilized chicken eggs. This was associated with the inhibition of TRAIL-induced NF-κB DNA binding activity and expression of CXCR4, Jagged1, Notch1, Sox2, and Nanog [62]. Notably, pancreatic CSCs treated with sulforaphane (5 μM) downregulated Notch1 expression, whereas gemcitabine (25 nM) treatment led to induction of Notch1.…”
Section: Sulforaphanementioning
confidence: 96%
“…These include the induction of cytoprotective proteins and carcinogen-detoxifying enzymes [56], inhibition of inflammatory responses [57], induction of tumor cell apoptosis [58], and the blockade of angiogenesis and metastasis [59]. In recent studies, sulforaphane was found to be effective in targeting breast [60], prostate [61,62], pancreatic [61], and leukemia [63] CSCs. The plasma levels of sulforaphane in rats reached 46 ng/ml after administration of 0.5 mg/kg, and human studies consistently indicated similar levels of 12 and 18.2 ng/ml in plasma after broccoli consumption [64][65][66].…”
Section: Sulforaphanementioning
confidence: 99%